Arctic Ekman pumping, Arctic Ocean, 2003-2014 - Gianluca Meneghello; John Marshall; Mary-Louise Timmermans; Jeffery Scott (Arctic Data Center, 2018)
Ekman pumping is one of the ocean circulation's main drivers. In the Arctic, Ekman pumping is strongly modified by the presence of sea-ice, which limits currents spin up by modulating the momentum transfer from the atmosphere to the ocean, as well as by the interaction of the surface currents with the ice cover itself. All these effects, and in particular the interaction of surface currents with the ice cover, are taken into account for the first time in this weekly Ekman pumping estimate, covering a region bounded by 60 degrees and 81.5 degrees North (N) for the period 2003-2014. Lack of satellite coverage does not allow us to go beyond 81.5 degrees N. The dataset provides estimates of the total Ekman pumping (we), as well as its wind-driven (alphaweair) and ice-driven (alphaweice) components over open ocean and ice-covered ocean respectively. The theoretical Ekman pumping over a completely ice-free ocean (weair) is additionally computed. Data are gridded over a 25km Equal-Area Scalable Earth (EASE) grid. For details and an application of this dataset in the study of the surface-current-ice interaction effect in the Beaufort Sea region please see G. Meneghello, J. Marshall, M.-L. Timmermans and J. Scott (2018) Observations of seasonal upwelling and downwelling in the Beaufort Sea mediated by sea ice. J. Phys. Oceanogr., 48(4), 795–805. doi:10.1175/JPO-D-17-0188.1